Implementation Of Dhuha Prayer Program In Construction Of Student Discipline Character At Smp Muhammadiyah 16 Lubuk Pakam - Lubis, Aidil Azhar Faizal; Fanreza, Robie (Cattleya Darmaya Fortuna, 2023)
The Dhuha prayer forms the character of students, which is when the Duha prayer is performed when people are busy with worldly activities and there are many lessons contained therein. The timing is a great time to meet face to face and build a personal relationship with God and receive special attention and affection from Him. According to Narwanti, character education is a system of instilling character values ​​in school members which includes components of knowledge, awareness or will, and actions to carry out these values, both towards God Almighty (YME), oneself, others, the environment, and nationality so that they become human beings. This research uses a descriptive qualitative approach. The population collected in this study were students of class VIII SMP Muhammadiyah 16 Lubuk. The sample for this research was 35 grade VIII students who were taken using student and teacher interview techniques, direct observation of the research location, and research documentation. To obtain data on the Implementation of the Dhuha Prayer Program for class VIII students, researchers used interview techniques, practice, and questionnaires or questionnaires. Meanwhile, the way to implement Discipline Character Formation is by direct application during the hours of Duha prayer activities Based on the findings of the researchers during the research at SMP Muhammadiyah 16 Lubuk Pakam.